1999
DOI: 10.1262/jrd.45.177
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Proliferation of Refined Chicken Circulating Primordial Germ Cells Cultured In Vitro

Abstract: Abstract. In recent years, much attention has been paid to the manipulation of primordial germ cells (PGCs) to produce transgenic chicken. For this purpose, the in vitro proliferation of PGCs would make gene targeting possible, promoting the efficiency of transgenes. However, few researches have been carried out on this topic. In the present study, we tried to culture chicken PGCs outside the body. The PGCs were isolated from circulating blood of chicken embryos by the method of Ficoll density centrifugation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Our data showed that chSCF2-BRL feeder cells improved the in vitro proliferation rate of chicken PGCs by fivefold compared with normal BRL feeder cells. Meanwhile, our data also demonstrated that chSCF1-BRL feeder cells did not sufficiently supported the in vitro proliferation of chicken PGCs, and this result was consistent with the previous studies [ 17 , 33 ]. Thus, chSCF2 was considered one of the essential factor for the in vitro proliferation of chicken PGCs.…”
Section: Discussionsupporting
confidence: 91%
“…Our data showed that chSCF2-BRL feeder cells improved the in vitro proliferation rate of chicken PGCs by fivefold compared with normal BRL feeder cells. Meanwhile, our data also demonstrated that chSCF1-BRL feeder cells did not sufficiently supported the in vitro proliferation of chicken PGCs, and this result was consistent with the previous studies [ 17 , 33 ]. Thus, chSCF2 was considered one of the essential factor for the in vitro proliferation of chicken PGCs.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous study suggested that some of growth factors such as LIF and bFGF might have influenced the proliferation of chicken circulating PGCs in vitro [13,14]. In the present experiment, therefore, we tried A of the area pellucida of developing embryos [1,2].…”
mentioning
confidence: 99%